Revisiting Zakat Distribution on Income Inequality and Welfare: The Malaysia Experience - Patmawati Ibrahim; Maimunah Ali; Mazliana Muridan; Amirul Iman Mohd Jazid (Universitas Negeri Surabaya, 2020)
This paper attempts to analyze the effects of zakat distribution on income inequality and welfare aspects of the poor Muslim society in Malaysia. The population of the study is the poor and hardcore poor of the zakat recipients in Selangor. Exploring the cross sectional micro level data of nine districts in Selangor, Malaysia, this study adopted Lorenz curve and Gini coefficient to represent positive measures of income inequality. However, these measures do not take into account the welfare effects of the distribution to the society. Hence, Atkinson index is adopted to represent the normative measures of inequality that takes into account the welfare effects of the zakat distribution to society. Results of the Gini coefficient and Lorenz curve have proven effectiveness of zakat distribution in reducing income inequality of the society. Whilst the theory of zakat says that zakat distribution will improve income inequality and welfare of the society, findings of the normative measures in this research show otherwise. Therefore, this study is extended with zakat distribution simulation model based on had kifayah. Results from the distribution simulation model proved the ability of zakat in narrowing down income inequality, reducing income loss and hence increasing the welfare of the society.